(untitled) (Eurasian Journal of Engineering and Technology, 2023)
Sudden change in the health status of vehicle drivers causes too many accidents. So we need an emergency system to control the car for preventing the driver from making an accident on the road Therefore, it’s crucial that the monitoring system for driver doesn’t limit or obstruct the driver’s movement are currently being created. Heartbeat monitoring devices ’Examples are presented in this review. The methods for detecting the heartbeat use wearable sensing devices, such as watches, rings, and shirts, as well as no wearable sensing devices, including steering wheels, seats, and other sorts of devices, are described in particular. The development of wearable technology, including the Apple Watch, is seen as a turning point in the use of driver monitoring systems. The issues with the existing smart watch- and smartphone-based systems are examined, along with the difficulties in implementing them in actual vehicles. We come to the conclusion that for detection methods utilizing in-cars gadgets and in-car cameras are anticipated to continue dominating, while future applications are anticipated to emerge for equipment that can identify health issues and anomalies while a person is just driving normally, the internet of Things (IOT) is the latest internet revolution, affecting all spheres of endeavor, including the health care industry. It improves the accessibility, safety, and patientcenteredness of healthcare, Using the Internet of Things in this work to monitor the patient’s health status remotely. An autonomous car parking system using ultrasonic sensors that dependent on the health status of the driver, which is determined through the heart rate sensor and Detect Arrhythmia from ECG Signal and using IOT System is presented in this paper. The system is capable of self-parking the vehicle. Using sensor coordination and can also park the vehicle remotely using a mobile phone application. The system looks for an acceptable parking space, detects obstacles, and then parks it using signals that sent from the controller to the motors. The suggested car parking system is a small module that may be incorporated into any type of vehicle